2023
DOI: 10.3390/su15107749
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Abies nephrolepis Materials for Restoration of Genetic Diversity in Mt. Gariwangsan Degraded Area

Abstract: This study proposes a strategy for selecting materials for Abies nephrolepis, a key subalpine species, to restore damaged forests in Mt. Gariwangsan while considering genetic diversity. The genetic diversity distribution of A. nephrolepis in Korea was evaluated using nuclear simple-sequence repeat (nSSR) markers and the genetic differences between populations were analyzed. A suitable genetic restoration population was selected and a strategy for selecting restoration materials was presented. The genetic diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…It is naturally distributed in the subalpine or boreal forests of eastern Russia, northeast China, and the Korean peninsula (Zhang et It is expected that the potential habitats of A. nephrolepis on the Korean peninsula will decrease to 36.4% by 2070-2099, and most regions in South Korea were expected to be inhabitable (Yun et al 2018). Populations of A. nephrolepis in South Korea had a low level of differentiation, only about 3-8% of total genetic variation resulted from the variation among populations (Woo et al 2008;Hong et al 2011;Seo and Lim 2022). These studies concluded that, in South Korea, only a few populations would be enough for conservation.…”
Section: Introductionmentioning
confidence: 99%
“…It is naturally distributed in the subalpine or boreal forests of eastern Russia, northeast China, and the Korean peninsula (Zhang et It is expected that the potential habitats of A. nephrolepis on the Korean peninsula will decrease to 36.4% by 2070-2099, and most regions in South Korea were expected to be inhabitable (Yun et al 2018). Populations of A. nephrolepis in South Korea had a low level of differentiation, only about 3-8% of total genetic variation resulted from the variation among populations (Woo et al 2008;Hong et al 2011;Seo and Lim 2022). These studies concluded that, in South Korea, only a few populations would be enough for conservation.…”
Section: Introductionmentioning
confidence: 99%
“…The Korea Forest Service noted that A. nephrolepis showed a decline rate of 31% in 2019–2020, which was estimated to be caused by higher temperature and droughts 23 It is expected that the potential habitats of A. nephrolepis on the Korean peninsula will decrease to 36.4% by 2070–2099, and most regions in South Korea were expected to be inhabitable 24 . Populations of A. nephrolepis in South Korea had a low level of genetic differentiation and only about 3–8% of total genetic variation resulted from the variation among populations 25 27 . These studies suggest that we could make the conservation more efficient by focusing on several populations.…”
Section: Introductionmentioning
confidence: 99%